PANCASILA SEBAGAI LANDASAN ILMU DALAM PENGEMBANGAN ILMU PENGETAHUAN DI INDONESIA - Mendrofa, Cindy Salni; Sinaga, Rudi Salam (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Pancasila, as the foundation of the Indonesian state, plays a central role in the development of science in Indonesia. This research examines how the values of Pancasila can serve as a moral and ethical foundation in the research and development of science. Through the application of the five principles of Pancasila, namely Belief in One God, Just and Civilized Humanity, the Unity of Indonesia, Democracy Guided by the Inner Wisdom in Deliberation and Representation, and Social Justice for All Indonesian People, the development of science is expected to not only advance technologically but also embody the values of humanity, social justice, unity, and divinity. This study also discusses the challenges and opportunities in integrating Pancasila as the foundation of science in the era of globalization. By facing global challenges such as climate change, poverty, and inequality, the application of Pancasila values in scientific research can become a solution to create sustainable and beneficial knowledge for all of humanity. Thus, this study is expected to contribute to strengthening the role of Pancasila as a guideline in the development of sustainable science in Indonesia.